Changes in retinal pigment epithelium related to cigarette smoke: possible relevance to smoking as a risk factor for age-related macular degeneration. - Ai Ling Wang; Thomas J Lukas; Ming Yuan; Nga Du; James T Handa; Arthur H Neufeld (PLoS ONE)
Age-related Macular Degeneration (AMD) is a major cause of central vision loss in the elderly and smoking is a primary risk factor associated with the prevalence and incidence of AMD. To better understand the cellular and molecular bases for the association between smoking and AMD, we determined the effects of Benzo(a)Pyrene (B(a)P), a toxic element in cigarette smoke, on cultured retinal pigment epithelia (RPE) and we examined the RPE/choroid from mice exposed to chronic cigarette smoke. We measured: mitochondrial DNA (mtDNA) damage, phagocytic activity, lysosomal enzymes, exosome markers and selected complement pathway components. In the presence of a non-cytotoxic dose of B(a)P, there was extensive mtDNA damage but no nuclear DNA damage. RPE phagocytic activity was not altered but there were increased lysosomal activity, exocytotic activity and complement pathway components. Retinas from mice exposed to cigarette smoke contained markers for mtDNA damage, exosomes and complement pathway components surrounding Bruch's membrane. Markers for these processes are found in drusen from AMD patients. Thus, smoking may cause damage to mtDNA and increased degradative processes in the RPE. These altered cell biological processes in the RPE may contribute to the formation of drusen in individuals who are cigarette smokers and underlie susceptibility to genetic mutations associated with AMD.